Insights into nutritionists' practices and experiences in remote Australian Aboriginal communities - Susan L. Colles; Suzanne Belton; Julie Brimblecombe (Elsevier, 2016)
Abstract Objective: To explore and describe methods of communication, education practices, perceived challenges and the potential role of nutritionists working in remote Australian Aboriginal communities in order to inform future public health efforts. Methods: Nutritionists who work or have worked in remote Aboriginal communities in Australia's Northern Territory within the past decade were identified via purposive and snowball sampling, and responded to a semi‐structured survey in 2012. Content and interpretive thematic analysis was used to generate themes. Results: Working approaches of 33 nutritionists are presented, representing 110 years of working experience in the Northern Territory. Emerging themes included: 'Community consultation is challenging', 'Partnering with local people is vital', 'Information is not behaviour', 'Localisation of nutrition education is important' and 'Evaluation is tricky'. Available time, training background and workforce structure were said to constrain practice and those nutritionists with longer experience described a more culturally competent practice. Conclusions: Modifications in structure, training and support of the public health nutrition workforce, facilitation of professional and cultural partnerships, outcome evaluation and localisation and evaluation of health messages may promote more meaningful nutrition communication in remote communities. Implications: Findings can inform further investigation into the structures needed to improve public health skills for nutritionists transitioning from mainstream practice into the challenging cross‐cultural context of Aboriginal health settings.